PENGARUH TINGKAT KETERGANTUNGAN DAERAH, TEMUAN AUDIT BPK, JUMLAH SATUAN KERJA PERANGKAT DAERAH, DAN UKURAN LEGISLATIF TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH - Ridwan, M; Yahya, M Rizal (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
This research aims to determine the influence of intergovernmental revenue, audit findings of the BPK, functional differentiation and legislative size to the level of disclosure of Local Government Financial Statements (LKPD) district/city in Aceh in 2015-2017. The population in this research is the Regency/city government in Aceh. The sample techniques in this study used the census method with 69 samples of the BPK-RI test Results Report of 2015-2017. The independent variables examined in this study were intergovernmental revenue, the BPK audit findings, the number of SKPD, and the legislative measures. While the dependent variable is the level of disclosure of Local Government Financial Statements (LKPD). The type of data used in this study is secondary data. The analyses used in this study were multiple linear regression. Subsequent data is processed by using the SPSS test tool. The results of the study showed the intergovernmental revenue, BPK audit findings, the number of SKPD, and the size of the legislature jointly impacted the level of LKPD disclosure. A partial intergovernmental revenue and the number of SKPD have a positive effect on LKPD disclosure rates, whereas BPK audit findings and legislative measures negatively affect LKPD disclosure rates.